The cellular inflammatory response associated with sulfur mustard induced delayed limbal stem cell deficiency and evaluation of tacrolimus treatment - Elina Berg; David Zadok; Ariel Gore; Maayan Cohen; Hila Gutman; Rellie Gez; Vered Horwitz; Shlomit Dachir; Tamar Kadar (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2019)
Purpose: To further investigate the inflammatory response as one of the leading factors in the development of delayed limbal stem cell deficiency, clinically manifested by corneal neovascularization , following sulfur mustard ocular exposure in rabbits and to evaluate potential therapy.  Materials and methods: Right eyes of rabbits were exposed to sulfur mustard vapor. Clinical examination was performed and the growth of corneal blood vessels was evaluated. Inflammatory cells (neutrophils, macrophages, antigen-presenting cells and T cells) were identified immunohistochemically. Tacrolimus (Prograf, Teva, 5mg/ml) an immuno-modulator drug, was tested via sub-conjunctival injection (50µl), started either before or after the development of neovascularization (72h and 4weeks, respectively) given once a week for 3weeks.  Results: Limbal stem cell deficiency, associated with inflammatory-related corneal neovascularization was developed starting at two weeks post-exposure. The cellular inflammation included elevation of neutrophils in the limbus at one week and later (2-4weeks) in the cornea. Antigen-presenting cells (predominantly dendritic cells) were seen in the limbus and the cornea at 1-4w, together with a massive accumulation of T cells that were correlated with neovascularization score. Treatment with tacrolimus was not effective in reducing the clinical signs or inflammatory infiltration.  Conclusions: Sulfur mustard-induced delayed limbal stem cell deficiency associated with corneal angiogenesis and inflammatory infiltration of neutrophils, dendritic cells and T cells in the limbus and cornea was observed. In spite of the association between T cells infiltration and corneal neovascularization, treatment with tacrolimus, did not reduce the inflammatory response and was not beneficial as a single drug therapy against the late sulfur mustard ocular injury.